Positive correlation between the quantity of Wharton's jelly in the umbilical cord and birth weight - Avsar A. Filiz; Bedir Rahime; H. Levent Keskin; Aktepe Keskin Esra (Elsevier, 2011)
Objective: To determine the possible protective effects of Wharton's jelly (WJ) in umbilical cord and fetal growth by investigating the relationship between the amount of WJ and fetal birth weight. Materials and Methods: This study enrolled 299 women who delivered after an uneventful pregnancy. After separation of the placenta, a 5 cm long section of umbilical cord was removed by scalpel. The weight of the cord section; the weight, volume, and density of its WJ; and the weight of the newborn and placenta were measured. Results: A significant positive correlation was found between WJ quantity, birth weight (p=0.002), and placental weight (p=0.003), whereas a significant negative correlation was observed for WJ density, fetal growth (p=0.035), and placental growth (p=0.002). WJ density was 1.63±0.27 g/mL. No significant correlation was found between the amount of WJ and weight gained during pregnancy (p=0.274) or maternal age (p=0.220). Conclusion: As the amount of WJ increases, fetal weight increases. Accordingly, the amount of WJ might be a factor that influences fetal growth.